Online Fanfiction for Language Teaching and Learning - Shannon Sauro (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Within the digital wilds, online communities, including communities of fans, represent a rich source of inspiration for the development of computer-mediated tasks and activities that can support alternative and creative approaches to language teaching and learning (Sauro, 2014). By its very nature, fanfiction grows out of fans' deep engagement with a television series, book, movie, performer, band, or other source of media. A challenge facing teachers and researchers is incorporating the enthusiasm and innovation inherent within these online spaces into a formal educational context. This presentation introduces recent research on language learning in the digital wilds. This is followed by an overview of research and pedagogical projects that have explored the development and implementation of fanfiction-inspired teaching materials. It then introduces research carried out by the FanTALES project.